The bible in the American short story - Stahlberg, Lesleigh Cushing (New directions in religion and literature, 2018)
The Bible in the American Short Story" examines Biblical influences in the post-World War II American short story. In a series of accessible chapters, Lesleigh Cushing Stahlberg and Peter S. Hawkins pair close-readings of short stories by leading contemporary writers such as Flannery O'Connor, Philip Roth, Tobias Wolff and Julia Valdez Quade with examinations of the biblical passages that they reference. Exploring episodes from the Hebrew Bible and the New Testament and both Jewish and Christian heritages, this book is an important contribution to understanding the influence of the Bible in contemporary literature